Speculation, heresy, and gnosis in contemporary philosophy of religion : the enigmatic absolute - Ramey, Joshua Alan, 1975- (Reframing Continental Philosophy of Religion, 2016)
This volume takes a multi-disciplinary approach to continental philosophy of religion, engaging with philosophy, theology, religious studies, anthropology, cultural studies, and new religious movements, to explore patterns of mind and mortality, existence and ecstasy, creativity and expression, political possibility and religious matrix.